Investigation of the correlation between perpendicular magnetic anisotropy, spin mixing conductance and interfacial Dzyaloshinskii–Moriya interaction in CoFeB-based systems. (8th October 2020) - Benguettat-El Mokhtari, I; Ourdani, D; Roussigné, Y; Mos, R B; Nasui, M; Chérif, S M; Stachkevich, A; Gabor, M S; Belmeguenai, M
Abstract: Correlation between interfacial Dzyaloshinskii–Moriya interaction (iDMI), perpendicular magnetic anisotropy (PMA) and spin pumping-induced damping was investigated in CoFeB-based systems grown by sputtering on Si substrates, using Pt, Ta, Cu, W and MgO capping layers. Vibrating sample magnetometer, Brillouin light scattering (BLS) and broadband ferromagnetic resonance techniques were combined for this aim. The CoFeB thickness dependence of iDMI and PMA constants, in CoFeB/X (where X = Pt, Cu/Pt, Ta/Pt or W/Al), revealed that only the CoFeB/Pt system presents a measurable iDMI and that the interfacial PMA is mostly similar except for the Ta/CoFeB/Ta/Pt system. Therefore, no clear correlation between the above-mentioned interfacially-driven and spin-orbit coupling related quantities was observed due to their different origins in our systems. An efficient sample design involving various spacer layers of variable thicknesses in Ta/CoFeB(1.5 nm)/Y/Pt (where Y = Cu, Ta, MgO) allowed evidence of a linear correlation between iDMI, PMA constants and the effective spin mixing conductance. The linear dependence, which could result from the narrow variation range of PMA and/or iDMI, is attributed to the similar interface orbital hybridizations involved in PMA, iDMI and spin pumping-induced damping.